Firm Value Predictor and the Role of Corporate Social Responsibility - Ismi Farida Siregar; Roekhudin Roekhudin; Lilik Purwanti (University of Merdeka Malang, 2018)
The firm value was an important part of the company to survive in the business world. The right decision to maximize capital had implications for increasing the firm value with the collaboration between management and owners. We examined the effect of managerial ownership, profitability, and firm size toward firm value. Also, we examined the moderation role of Corporate Social Responsibility (CSR) disclosure in strengthening the effect of managerial ownership, profitability, and firm size on firm value. The analytical technique used the analysis of moderation regression. The research population was manufacturing company sub-sector of consumer goods industry listed in Indonesia Stock Exchange (IDX), and the sample was selected using purposive sampling technique with the number of samples observation for 14 companies. We found that managerial ownership and firm size had a negative effect on firm value. Profitability gave a significant positive effect on firm value. CSR disclosure proved to strengthen the relationship of profitability to firm value, but CSR weakens the relationship between managerial ownership and firm size toward firm value.JEL Classification: G32, M14DOI: https://doi.org/10.26905/jkdp.v22i3.1804